PENERAPAN SOFTWARE BAHASA R UNTUK MENINGKATKAN MOTIVASI DAN PEMAHAMAN STATISTIKA MAHASISWA (JURNAL LEMMA, 2020)
AbstractStudents' abilities can be developed through lectures, one of which is variable Statistics. For the maximum tuition required of a material that can support course lectures. In Universitas Islam, Raden Rahmat, students only rely on one textbook only when the lectures, so the motivation and low student interest in learning. One way that can help make it easier for students is the use of textbooks using R software. This research aims to develop textbooks using R software that is valid, practical, and effective in statistics subjects in Universitas Islam Raden Rahmat. This study is a research development. This textbook was developed using the 4D model (define, design, develop, and disseminate). Phase disseminate not done. The data was collected with the validation and testing of the Textbook. The textbook is validated by the lecturer and expert statistics, as well as Indonesian lecturers. Tests were carried out on mathematics education students at Universitas Islam Raden Rahmat to know the textbook's praktikalitas and effectiveness. The results showed that: 1) Textbook is valid (including the content and construct validity) of the validator's point of view, 2) the use of Textbook in the lecture did not experience significant barriers. According to students and lecturers, the book is a practical work, and 3) Textbooks have been effective. This is evident from the activities of students and high motivation to learn after the lecture. Keywords: Development, Statistics, Text Book. AbstrakKemampuan mahasiswa dapat dikembangkan melalui perkuliahan, salah satunya pada mata kuliah  Statistik a. Agar perkuliahan maksimal diperlukan suatu materi yang dapat menunjang perkuliahan. Di Universitas Islam Raden Rahmat mahasiswa hanya mengandalkan satu buku ajar saja saat perkuliahan, sehingga motivasi dan minat belajar mahasiswa rendah. Salah satu cara yang dapat membantu memudahkan mahasiswa adalah penggunaan buku ajar menggunakan software R. Tujuan penelitian ini adalah untuk mengembangkan buku ajar menggunakan software R yang valid, praktis dan efektif dalam mata pelajaran Statistik a di Universitas Islam Raden Rahmat. Penelitian ini merupakan penelitian pengembangan. Buku ajar ini dikembangkan dengan menggunakan model 4D (define, design, develop, dan disseminate). Fase disseminate tidak dilakukan. Pengumpulan data dilakukan dengan validasi dan pengujian buku ajar. Buku ajar disahkan oleh dosen dan pakar Statistik a, serta dosen Bahasa Indonesia. Pengujian dilakukan pada mahasiswa manajemen Universitas Islam Raden Rahmat untuk mengetahui praktikalitas dan keefektifan buku ajar. Hasil penelitian menunjukkan bahwa: 1) buku ajar valid (termasuk validitas isi dan konstruk) dari sudut pandang validator, 2) penggunaan buku ajar dalam perkuliahan tidak mengalami hambatan yang berarti menurut mahasiswa dan dosen; dan 3) buku ajar sudah efektif. hal tersebut terlihat dari aktivitas mahasiswa dan motivasi belajar yang tinggi setelah perkuliahan. Kata Kunci: Pengembangan, Statistika, Buku Ajar.